Yeast Fermentate-Mediated Reduction of Salmonella Reading and Typhimurium in an in vitro Turkey Cecal Culture Model - Feye, Kristina M.; Dittoe, Dana K.; Rubinelli, Peter M.; Olson, Elena G.; Ricke, Steven C. (Frontiers in Microbiology, 2021)
Salmonella Reading is an ongoing public health issue in the turkey industry, leading to significant morbidity in humans in the United States. Pre-harvest intervention strategies that contribute to the reduction of foodborne pathogens in food animals, such as the yeast fermentation metabolites of Original XPC (XPC), may become the key to multi-hurdle farm to fork strategies. Therefore, we developed an anaerobic in vitro turkey cecal model to assess the effects of XPC on the ceca of commercial finisher tom turkeys fed diets void of XPC and antibiotics. Using the in vitro turkey cecal culture method, ceca were tested with and without XPC for their anti-Salmonella Reading and the previously defined anti-Typhimurium (ST97) effects. Ultimately, the anti-Salmonella effects were independent of serovar (P > 0.05). At 0 hours post inoculation (hpi), Salmonella levels were equivalent between treatments at 7.3 Log10 CFU/ml, and at 24 hpi, counts in XPC were reduced by 5 Log10 CFU/mL, which was 2.1 Log10 lower than the control (P < 0.05). No differences in serovar prevalence existed (P > 0.05), with a 92% reduction in Salmonella positive XPC treated ceca cultures by 48 hpi (P < 0.05). To evaluate changes to the microbiota independent of the immune response, the 16S rDNA was sequenced using the Illumina MiSeq platform. Data indicated a profound effect of time and treatment for the reduction of Salmonella irrespective of serovar. XPC sustained diversity metrics compared to the control, demonstrating a reduction in diversity over time (Q < 0.05).